Is Artificial Intelligence safe without regulations? - Malhotra, Ash (Archives of Business Research, 2019)
Nothing has brought so much excitement in disruptive technology as the Artificial Intelligence (AI). It is creeping into every aspect of human life. There is no area of human existence which remains untouched by artificial intelligence whether it is education, medicine, research, social life and others. In fact, it is interweaving the life on planet and promoting globalisation to make the world into a global village. The benefits are enormous and so are the risks. The two latest threats of AI looming on the horizon are the Trade war between US and China, and the technological manipulation of US elections. These are tip of the iceberg but deeper could lurk more predators waiting to misuse and abuse AI to promote their devious interest. Management thoughts are taking backseat allowing AI to go amuck like a runaway trojan horse. There is lot of confusion in reflecting the impact of the AI concepts by policy thinker due to lack of research. This paper has attempted to investigate the subtle interpretation of AI in minds of the public through the secondary research, empirical evidence and online survey indicates to understand whether there is a need for AI regulations. The intention is to open a platform for more research, discussion and collaborative environment so that the runaway AI trojan horse has the necessary positive resistance to keep on track towards making safe planet. The initial finding confirms that AI fears are real in people’s mind and regulations are desired. However, deeper examination may be required to support and validate the findings of this paper.